Rancang Bangun Alat Uji Muai Panjang Material Logam Berbasis Pemanas Elektrik dan Dial Indikator - Santoso, Hadi; Arie Linory; Marhadi Budi Waluyo; Andi Rosman (Universitas Islam Negeri Alauddin Makassar, 2023)
Has been design of a length expansion test instrument for metal material based on electric heaters and dial gauge with iron rods metal as the test material. The purpose of this research is to design a metal material length expansion instrument and analyze the feasibility of the instrument. The main components of this expansion test tool use an electric heater and a dial gauge. The function of the electric heater is as a heater on the test specimen, while the dial indicator is used as a measuring device which is an indicator of the long expansion phenomenon. After testing the iron metal, it showed that this instrument worked well in observing the long expansion phenomenon qualitatively. However, the quantitative results show differences, where the coefficient is measured (0.000045/℃) and reference (0.000012/℃).